Mid-urethral slings on YouTube: quality information on the internet?. Issue 6 (June 2016) - Larouche, Maryse; Geoffrion, Roxana; Lazare, Darren; Clancy, Aisling; Lee, Terry; Koenig, Nicole; Cundiff, Geoffrey; Stothers, Lynn
Abstract Introduction and hypothesis Scant literature exists about the quality of urogynecological content on social media. Our objective was to measure the accuracy and comprehensiveness of YouTube videos related to mid-urethral sling (MUS) procedures. Methods YouTube was searched using the terms "mid-urethral sling, " "vaginal tape, " "TVT, " "TOT, " "TVT surgery, " and "TOT surgery." Duplicates and videos with less than 1, 000 views were excluded. We developed a standardized questionnaire for this project, assessing each video's target audience, main purpose, relevance, informed consent elements, surgical steps, and bias. The primary outcome was the presence of all elements of informed consent. Inter-rater reliability (IRR) was calculated using the Fleiss' kappa statistic. Descriptive statistics were also obtained. Results Five reviewers each rated 56 videos. Mean IRR was moderate (Fleiss' kappa 0.58 ± 0.24). Video content was classified as physician educational material (67.9 %), patient information (16.1 %), advertisement (10.7 %), lawsuit recruitment (1.8 %), and unclear (3.6 %). MUS was the primary topic for 82.1 % of the videos. The remainder discussed other types of anti-incontinence procedures or prolapse surgery. None of the videos mentioned all four elements of informed consent. Of 32 videos demonstrating surgical technique, none showed the complete list of pre-determined surgical steps. The mean number of listed steps was 7.6/16. Only four videos mentioned at least one post-operative patient instruction. A marketing element was shown in 26.8 % of videos. Conclusions Patient information about MUS on YouTube is lacking and often biased. Physicians and students viewing YouTube videos for educational purposes should be cognizant of the variability in the surgical steps demonstrated.